2013
DOI: 10.1158/1055-9965.epi-13-0625
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiovascular Comorbidity on Ovarian Cancer Mortality

Abstract: BACKGROUND A retrospective cohort study utilizing prospectively collected data was conducted from August 2003 until March 2008 at M. D. Anderson Cancer Center. It is unknown whether cardiovascular comorbidity and chronic stress impact ovarian cancer outcome, which remains poor despite advances in therapy. The purpose of this study was to determine whether cardiovascular disease and markers that may be associated with stress are also associated with survival in ovarian cancer patients. METHODS Participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Prior research on the impact of comorbidities on stage at diagnosis has yielded inconsistent findings, but our results align with much of the ovarian cancer-specific research. [36][37][38][39] Prior research has found that having multiple comorbidities is associated with advanced stage at diagnosis and less aggressive treatment courses for ovarian cancer; both have been shown to increase the risk of death from ovarian cancer by 40%. [36][37][38][39] Our nonsignificant findings also align with the theory of competing demand, which postulates comorbidities distract patients and physicians from noticing tumor growth and cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on the impact of comorbidities on stage at diagnosis has yielded inconsistent findings, but our results align with much of the ovarian cancer-specific research. [36][37][38][39] Prior research has found that having multiple comorbidities is associated with advanced stage at diagnosis and less aggressive treatment courses for ovarian cancer; both have been shown to increase the risk of death from ovarian cancer by 40%. [36][37][38][39] Our nonsignificant findings also align with the theory of competing demand, which postulates comorbidities distract patients and physicians from noticing tumor growth and cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…(28) Interestingly, CRF-driven markers of prolonged sympathetic activity, such as elevated resting heart rate, have been shown to be prognostic for survival in metastatic breast cancer (29) and in ovarian cancer (HR=1.02 for every HR unit increase (CI=1.01-1.04). (30)…”
Section: Discussionmentioning
confidence: 99%
“…The AYA HOPE index expanded the existing cardiovascular, neurologic, gastrointestinal and renal categories in the Charlson and NCI indices and added mental health and obesity/overweight categories that have not been included in the existing comorbidity indices, but are important to health outcomes and can affect treatment, service needs, and survival for AYA cancer patients. (2124) For example, the AYA HOPE index captured neurological conditions, such as neuropathy, extremity issues, epilepsy, syncope, and cranial nerve issues that may influence therapy or be associated with needs for health services and quality of life in AYA cancer survivors. Our study is the first, to our knowledge, to examine the association of comorbidities and service needs and found that AYA cancer survivors with comorbidities identified by AYA HOPE index were more likely than those without comorbidities to need mental health and pain management services and AYA survivors with more than 2 comorbidities were more likely than those without comorbidity to have fair/poor general health status.…”
Section: Discussionmentioning
confidence: 99%